PERAN ORGANISASI KEMASYARAKATAN SEBAGAI MEKANISME CHECK AND BALANCE TERHADAP KEKUASAAN PRESIDEN PERSPEKTIF KEPEMIMPINAN ISLAM - Nurul Muthmainnah; Nur Asriyani Ridwan; Aqna Nely Azqia Muqtar; Kurniati Kurniati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to examine the position, role, and impact of community organizations (organisasi kemasyarakatan or ormas) in overseeing presidential power from the perspective of Islamic leadership. The issues addressed include the legal standing of ormas within the system of presidential oversight, the various roles they perform in monitoring government policies, and the effects of such oversight on governance. This research employs a normative legal research method using statutory, conceptual, historical, and comparative approaches. The data were collected through library research consisting of primary, secondary, and tertiary legal materials and were analyzed using a descriptive qualitative method. The findings reveal that ormas occupy a strong position as elements of civil society that possess both legal and moral legitimacy to supervise presidential authority. Their functions are carried out through social control, the articulation of public aspirations, public policy advocacy, political education, and efforts to strengthen constitutional accountability. From the perspective of Islamic leadership, such oversight is grounded in the principles of amanah (trustworthiness), justice, consultation (shura), and amar ma'ruf nahi munkar (enjoining good and forbidding evil). The impact of this oversight is reflected in increased transparency, accountability, and the overall quality of governance, while also serving as a mechanism to prevent the abuse of power. Therefore, the oversight conducted by ormas functions not only as an instrument of democracy but also as an embodiment of Islamic leadership values in promoting a just, trustworthy, and welfare-oriented government.